Kronik venöz yetmezlikli hastalarda Türkçe Aberdeen Variköz Ven Anketisorgulamasının geçerlik ve güvenirlik değerlendirmesi - (:unkn) unknown (My University, 2017)
Amaç: Alt ekstremitede venöz hastalığı olanlarda yaşam kalitesini ölçmek için Türkçeye çevrilmiş Aberdeen Variköz Ven Anketi'nin (AVVA) güvenirliği ve geçerliği değerlendirildi.Hastalar ve Yöntemler: Türk AVVA variköz damarlarla ilgili 13 sorudan oluşmaktadır. Bacakta venöz hastalığı olan 50 hastada (18 erkek, 32 kadın; ort. yaş 31.2±7.8 yıl; dağılım 20-50 yıl) Türkçe AVVA'nın fizibilite, güvenirlik ve geçerliği değerlendirildi. Türkçe AVVA'nın testi ve tekrar testi 5 ila 7 gün aralıklarla yapıldı. Anketin test, tekrar test güvenirliği Kappa istatistiği ile belirlendi. Eş zamanlı geçerlik için Venöz Yetmezlik Epidemiyolojik ve Ekonomik Çalışma (VEINES)-yaşam kalitesi ile ilişkisi değerlendirildi. Eş zamanlı geçerlik Spearman korelasyon katsayısı ile ölçüldü.Bulgular: Anketin test-tekrar test güvenirliğinin iyi - mükemmel arasında olduğu belirlendi . Türkçe AVVA'nın geçerliği iyi olarak bulundu (rho=-0.678, p<0.001).Sonuç: Çalışma sonuçlarımız AVVA anketinin Türkçe versiyonunun geçerli ve güvenilir olduğunu ve venöz hastalığı olanlarda sağlıkla ilgili yaşam kalitesi ölçümünde uygulanabileceğini desteklemektedir.

Objectives: This study aims to evaluate the reliability and validity of the Aberdeen Varicose Vein Questionnaire (AVVQ ) translated into Turkish to assess the quality of life in patients with venous disease in the lower extremity.Patients and methods: The Turkish AVVQ consists of 13 questions about the varicose veins. The feasibility, reliability, and validity of the Turkish AVVQ in 50 patients (18 males, 32 females; mean age 31.2±7.8 years; range, 20 to 50 years) with leg venous disease were evaluated. Testing and re-testing of the Turkish AVVQ were performed at 5 to 7 day-intervals. The test-retest reliability of the questionnaire was determined using the Kappa statistic. Concurrent validity was evaluated for the Venous Insufficiency Epidemiological and Economic Study (VEINES)-quality of life. Simultaneous validity was measured using the Spearman correlation coefficient.Results: The test-retest reliability was found to be between good and excellent . The validity of the Turkish AVVQ was found to be good (rho: -0.678, p<0.001).Conclusion: Our study results show that the Turkish version of the AVVQ questionnaire is valid and reliable and that patients with venous disease can be applied in the measurement of health-related quality of life.
Evaluation of the validity and reliability of the Turkish Aberdeen Varicose Vein Questionnaire in patients with chronic venous insufficiency
Keywords: Cerrahi